Analysis of Lignin Aromatic Structure in Wood Fractions Based on IR Spectroscopy. (2nd September 2016) - Huang, Yu; Wang, Zhiguo; Wang, Linshan; Chao, Yuesheng; Akiyama, Takuya; Yokoyama, Tomoya; Matsumoto, Yuji
Abstract : In our previous studies, a method of quantitative analysis of lignin structure by IR spectroscopy with direct use of wood meal was developed which can be apply to a wide range of wood species. Lignin structure deposition in different fractions in the same wood sample also has characteristic diversity and differences. In this study, quantitative analysis of lignin structure by IR spectroscopy was used to determine whether it can be applied to different fractions in the same wood sample. Finely milled beech wood was fractionated by stepwise extraction using aqueous dioxane and followed by subsequent dimethyl sulfoxide (DMSO)/LiCl solvents with increasing LiCl concentrations. The results showed that fractions of the peak area ratio of log(1595/1509) fit a linear relationship with different wood species very well. Therefore, log(1595/1509) could be used not only with different wood species but also with different fractions from the same wood. For 1509/1460, log(1275/1220), 1130/1030 and 835/(835+815), different fractions deviated from the original relationship obtained from different wood species.